What drives growth responses of nitrogen and phosphorus (co-)limited primary producer communities? - Redoglio, Andrea; Sperfeld, Erik (Frontiers in Ecology and Evolution, 2024)
The growth of autotroph communities is frequently (co-)limited by essential nutrients such as nitrogen (N) and phosphorus (P). Several mechanisms have been proposed to explain the observed co-limitation patterns at different levels of biological organization, especially at the biochemical level for individual species. When considering communities, the presence of different species and functional groups with contrasting physiologies and nutrient requirements leads to a more difficult understanding of the mechanisms involved in nutrient (co-)limitation. To investigate what drives co-limitation patterns and possible underlying mechanisms based on biomass responses in autotroph communities, we grew phytoplankton communities differing in species composition in experimental microcosms on three N:P ratios to impose different limiting conditions. Afterwards, N, P, both, or none were factorially supplied to the communities to test which nutrients were limiting growth. We measured the biovolume of single species in the communities to assess how they responded to nutrient additions and compared it to the response of the overall community biovolume. The types of nutrient (co-)limitation identified, i.e. the factorial limitation scenarios for community biomass were single N limitation or simultaneous co-limitation by N and P, and were strongly driven by the dominant species. The phytoplankton species in the communities responded differently to the nutrient addition treatments, i.e. they showed contrasting limitation outcomes and therefore likely different nutrient requirements. Our experiment indicates that phylogenetically distantly-related phytoplankton species grown in a community can have different resource use efficiencies and thus can be limited by different nutrients. We suggest that the dominance of species or groups with similar traits in nutrient requirements and acquisition is one of the leading mechanisms that determines the biomass pattern of nutrient (co-)limitation observed at the community level. This work also highlights the potential of predicting community growth limitation outcomes based on knowledge of nutrient use efficiencies of one or few dominant species, which can be a suitable tool for lake restoration and oligotrophication efforts.